Exo70 is an independent prognostic factor in colon cancer - Xiao, Li (Sci Rep, 2017)
Exo70, a key component of the Exocyst complex, plays important roles in human cancer progression beyond exocytosis. However, the expression of Exo70 and its prognostic value for patients with colon cancer has not been well investigated to date. In this study, we observed that the mRNA and protein levels of Exo70 were upregulated in 11 of 13 colon cancer tissues, compared with their normal counterparts, which was validated by immunohistochemical analysis in a tissue microarray containing 89 pairs of colon cancer tissues and the matched adjacent normal tissues. Statistical analysis revealed that Exo70 expression is positively correlated with tumor size, invasion depth, TNM stage and distant metastasis. Kaplan-Meier survival analysis showed that colon cancer patients with higher Exo70 expression have a poorer clinical outcome than those with lower Exo70 expression. Multivariate Cox regression analysis revealed that Exo70, age and distant metastasis were there independent prognostic factors for overall survival rate of colon cancer patients. Through gain- and loss of Exo70 in colon cancer cells, we found that Exo70 could enhance the migration ability of colon cancer cells. Taken together, our studies revealed that Exo70 might be a promising negative prognostic factor and a potential therapeutic target for colon cancer.